PENINGKATAN PEREKONOMIAN MASYARAKAT DESA THEKELAN MELALUI REVITALISASI PEMGEMBANGAN GREENHOUSE DESA - Indah Fajarini S. W.; Muhammad Ihlashul Amal; Sri Utami; Mei Lina (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Greenhouses play a critical role in meeting food needs by modifying environmental conditions to support plant maintenance and optimal land use efforts. Thekelan Village's greenhouses have not been fully utilized due to a lack of adequate knowledge and skills in managing and using greenhouses. This service aims to provide information and training on the revitalization and optimization of greenhouse functions. This service employs the method of gathering representatives of the target community in Thekelan Hamlet for direct education and practice. The outcomes of this service activity demonstrate that the community is eager to participate in workshops and training. The target community learns new skills and is able to operate the greenhouse effectively. Planting food crops is considered successful because it can help to meet the food and economic needs of the surrounding community. Planting horticulture is considered successful because it can help to meet the food and economic needs of the surrounding community. Abstrak Greenhouse memiliki peranan penting pemenuhan kebutuhan pangan melalui manipulasi kondisi lingkungan untuk mendukung pemeliharaan tanaman dan upaya pemanfaatan lahan secara optimal. Keberadaan greenhouse di Desa Thekelan belum maksimal karena kurangnya pengetahuan dan keterampilan yang memadai dalam pengelolaan dan pengunaan greenhouse dengan baik. Pengabdian ini dimaksudkan untuk memberikan pengetahuan dan pelatihan mengenai revitalisasi dan pengoptimalan fungsi greenhouse. Metode yang digunakan dalam pengabdian ini dengan mengumpulkan perwakilan masyarakat sasaran di Dusun Thekelan untuk diberikan edukasi dan praktik secara langsung. Hasil kegiatan pengabdian ini menunjukkan bahwa masyarakat antusias dalam mengikuti workshop dan pelatihan, masyarakat sasaran memperoleh ilmu baru dan mampu memfungsikan greenhouse dengan baik. Praktik penanaman tanaman pangan dinilai berhasil dikarenakan dapat mendukung pemenuhan kebutuhan pangan dan ekonomi masyarakat sekitar.